Survival analysis of patients with rare tumors of the uterine corpus – carcinosarcomas - Stevanović, Nemanja; Mandić, Aljoša; Maričić, Slobodan; Nadj, Gabriel Stefan; Maksimović, Tamara; Stanulović, Nevena; Čančar, Vladimir; Rodić, Milan (Vojnosanitetski pregled, 2024)
Background/Aim. Uterine carcinosarcoma (UCS), formerly known as malignant mixed Müllerian tumor, is a rare, aggressive malignancy of the female genital tract. The aim of this study was to analyze the most important clinical and pathohistological characteristics of UCSs on operated patients, as well as to determine which of those factors are affecting progression-free survival (PFS) and overall survival (OS) of patients. Methods. The study was conducted as a retrospective analysis of medical data documentation of patients with a diagnosis of UCS who were surgically treated at the Department of Gynecology, Clinic for Operative Oncology, Oncology Institute of Vojvodina, Sremska Kamenica, Serbia, in 10 years’ period (from the beginning of 2009 to the end of 2018). The analysis included data for a total of 31 patients. Results. Of all the examined parameters (age of the patient, clinical stage of the disease, histological grade, depth of myometrial invasion, and lymphovascular invasion – LVI), the greatest influence on the choice of therapeutic procedure had a histological tumor grade. Conclusion. Our research showed the joint influence of the examined clinical and pathohistological factors on PFS and OS of patients with UCS. The only independent parameter that showed a statistically significant impact on survival is LVI.